Peningkatan Pemahaman Teks Bahasa Arab Melalui Metode (SQ3R) - Parhan, Parhan; Abdul Jalil, Muhammad; Idrus, Idrus; Mudiono, Mudiono (Ta'limi | Journal of Arabic Education and Arabic Studies, 2022)
The purpose of this study was to determine how the application of the SQ3R method in improving understanding of Arabic texts and to determine the extent to which the understanding of Arabic text was increased through the SQ3R method. This study used a qualitative approach with a classroom action research (CAR) strategy. The subjects of this study were students of class VII B MTs Nurul Yaqin Legok Tangerang. Sources of data used: (1) informants, namely Arabic teachers in class VII B MTs Nurul Yaqin who are easy to communicate with (2) data or documents, in the form of reading texts, photos of teaching and learning activities, student test results, transcripts of interviews with students and teacher. The data collection technique used was data triangulation which included: (1) observation / observation, (2) interviews, and (3) documentation (4) written test assessments. The research process was carried out in 2 cycles, each cycle consisting of four stages, namely: (1) planning the action, (2) implementing the action, (3) observing, and (4) analyzing and reflecting. Based on the results of research carried out that the SQ3R method was able to improve students' understanding of Arabic text. With an average acquisition of 64 on the pre-test results, then increased in cycle I with an average of 84, then increased again in cycle II with an average result. Average 95.5. with an average comparison of 20 between the pre-test and post-test cycle I, and the comparison between cycle I and cycle II, namely 11.5.